Optimasi Hydroxypropyl Methylcellulose dan Xanthan Gum pada Tablet Floating-Mucoadhesive Gliclazide Metode Desain Faktorial (Optimization of Hydroxypropyl Methylcellulose and Xanthan Gum on Floating-Mucoadhesive Gliclazide Tablet using Factorial Design) - Eva Setyorini; Eka Deddy Irawan; Lusia Oktora Ruma Kumala Sari (Pustaka Kesehatan, 2016)
Gliclazide is one of the drugs used for type 2 diabetes mellitus treatment. It requires frequent dosing which is why gliclazide need to be formulated into preparations using a controlled release drug delivery system. This study aimed to determine the optimum composition of hydroxypropyil methylcellulose (HPMC K4M) and xanthan gum polymer combination for gliclazide tablet. Tablets that have been produced were evaluated for tablets physical characterization, homogenity test, dissolution test, floating lag time, and mucoadhesive test. Tablets were optimized using a factorial design and the data were analyzed using design expert trial 9.0.6. The results showed that the optimal formulation for polymer combination in gliclazide tablet was 122.267-140.000 mg for HPMC K4M and 80.659-90.000 mg for xanthan gum.   Keywords: gliclazide, HPMC K4M, xanthan gum, floating-mucoadhesive system, factorial design.